Beta-blockers are associated with incident heart failure: a secondary analysis of the systolic blood pressure intervention (SPRINT) trial. (25th November 2020) - Silverman, D.N; De Lavallaz, J.D.F; Plante, T.B; Goyal, P; Infeld, M.M; Meyer, M
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT) evaluated whether a blood pressure (BP) goal of less than 120mmHg versus less than 140mmHg would reduce cardiovascular outcomes in subjects with at least one cardiovascular risk factor and without heart failure. Participating investigators were encouraged to use any antihypertensive medication class with a strong evidence base. The SPRINT trial was halted early due to a lower rate of the composite primary outcome in the 120mmHg group, which was mainly driven by a reduction in heart failure (HF). Objective: As there is a concern that beta-blocker use may be associated with an excess risk for incident HF in subjects with a normal left ventricular systolic function, we evaluated the association between beta-blocker use and HF. Beta-blockers were compared with other major classes of antihypertensive medications. We also studied the association of antihypertensive class with loop-diuretic initiation. Methods and results: In the 9, 012 subjects, without HF at baseline, the association of beta-blocker exposure and incident HF was examined using time-variant competing risk analysis. Beta-blocker exposure was associated with an increased HF risk (HR 1.18; CI 1.07–1.30; p<0.001) and more frequent and earlier loop diuretic-use compared to other antihypertensive agents (both p<0.01). Sensitivity analyses of propensity-score matched cohorts confirmed a strong association of beta-blocker use and HF. Other major antihypertensive medication classes did not show this association. Conclusions: Beta-blocker exposure was associated with a higher incidence of HF in hypertensive subjects without HF at baseline. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health